Current Harmonic Suppression Algorithm for Asymmetric Dual Three-Phase PMSM - Zhihong Wu (Applied Sciences, 2020)
Based on the vector space decomposition (VSD) transformation, the currents of an asymmetric dual three-phase permanent magnet synchronous motor (ADT-PMSM) with isolated neutral points are decoupled into the torque, producing α-ß components in the fundamental subspace and the loss-producing x-y components in the harmonic subspace. In order to suppress the current harmonics, a feedforward voltage compensation that is calculated according to the dead time, turn on/off time, and the voltage drop is added to the reference voltage of the control algorithm. Due to the limitations of the feedforward voltage compensation method, a feedback current control loop is set up in the x-y subspace, where an improved resonant controller is adopted to generate the compensation voltage. The improved resonant controller can achieve a high gain at a specific frequency. The experimental results verify the effectiveness of the proposed method.